Composite sandwich panel with multifunction of load bearing, heat insulation, and thermal protection. (October 2015) - Yin, Changping; Zheng, Qing; Zeng, Jingcheng; Yang, Jinshui; Xiao, Jiayu
Integrative sandwich panels with multifunction of load bearing, thermal protection, and heat insulation are manufactured through co-injection resin transfer molding process. These panels have a polymethacrylimide foam core for heat insulation and two composite layers made of carbon/epoxy for load bearing and carbon/phenolic for thermal protection. In co-injection resin transfer molding process, the epoxy resin and phenolic resin are synchronously injected and cured in order to make integrative structures and improve the properties of the interface between different layers. The influence of main factors in the process of co-injection is investigated: the vacuum assistance is indispensable to improve the efficiency of manufacture and guarantee the properties of the products, volume fraction of carbon fiber plays the main role in determining size accuracy of the product, adjusting injection pressure is a simple and efficient way to adjust the infusion time of resin, while injection temperature has smaller influence in the features of manufacture. The mechanical properties of sandwich panels manufactured through co-injection resin transfer molding process and multi-step process are tested and compared to validate the advantage of the co-injection resin transfer molding process. The test shows that the in-plane compressive strength, three-point flexural strength, and interface shear strength are all improved by the co-injection resin transfer molding process. Co-injection resin transfer molding process is proved to be a feasible and efficient way to manufacture the integrative sandwich panel with good interface features.